Alkali lignin loaded copper sulfide nanoparticles, photo-thermal electric device and preparation method and application of photo-thermal electric device
By using alkali lignin-loaded copper sulfide nanoparticles and thermoelectric functional hydrogels in photothermal conversion technology, the problems of low photothermal conversion efficiency and insufficient utilization of near-infrared light in the prior art are solved, and efficient photothermal conversion and long-life photothermal conversion are achieved.
Patent Information
- Application Number
- CN202411459288.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-10-18
AI Technical Summary
The existing photothermal conversion technology has low photothermal conversion efficiency within a wide spectrum response range and insufficient utilization of near-infrared light, resulting in the performance of photothermal electrical devices not meeting expectations.
Alkaline lignin-loaded copper sulfide nanoparticles are used as the photothermal conversion material, and prepared by adsorbing alkali lignin nanoparticles with Cu2+ in copper salt and reacting with S2- to form alkali lignin-loaded copper sulfide nanoparticles and assembled with hydrogels with thermoelectric functions to build efficient photothermal electrical devices.
It improves the photothermal conversion efficiency and long-term stability, enhances the performance of photothermal electrical devices, achieves more efficient photoelectric conversion and electrical energy output, and extends the service life of the equipment.
Smart Images

Figure CN119522011A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of photothermal-electric conversion, and more specifically, relates to an alkali lignin-loaded copper sulfide nanoparticle, a photothermal-electric device, and a preparation method and application thereof. Background Art
[0002] Against the backdrop of growing global energy demand and increasingly severe environmental problems, research on energy conversion technology has become a very urgent scientific issue. Photothermal-electric conversion technology, as an innovative and green way of converting new energy, has shown unprecedented potential in the exploration of renewable resources. This technology can not only capture living environment, industrial production processes, solar radiation, and low-grade thermal energy (temperature below 100 °C), but also can synergistically convert the captured light energy and thermal energy into electrical energy, greatly broadening the boundaries of energy utilization.
[0003] The core advantage of photothermal-electric conversion technology lies in its unique dual mechanism of photothermal conversion and thermoelectric conversion, in which photothermal conversion converts light energy into thermal energy, while thermoelectric conversion further converts thermal energy into electrical energy, thereby realizing the conversion of light energy into electrical energy. However, most current photothermal-electric conversion technologies mainly use visible light and some ultraviolet light for photothermal conversion, and the utilization of the important near-infrared light band is still insufficient, so the performance of the prepared photothermal electric devices has not reached the expected level. Therefore, the development of photothermal conversion materials with near-infrared absorption is an inevitable choice. Such materials can broaden the spectral response range and improve the photothermal conversion efficiency to achieve better photoelectric conversion and complete more efficient electrical energy output, thereby achieving the purpose of significantly improving the photothermal-electric performance of the prepared photothermal electric devices. For example, Xie Yuanxiang et al. (Xie Y, Qian Y, Li Z, et al. Near-infrared-activated efficient bacteria-killing bylignin-based copper sulfide nanocomposites with an enhanced photothermaleffect and peroxidase-like activity[J]. ACS Sustainable Chemistry&Engineering, 2021, 9(18): 6479-6488.) synthesized a lignin-copper sulfide nanocomposite using lignin sulfonate as a growth template and stabilizer. The material exhibited enhanced photothermal performance under near-infrared light activation. When irradiated with near-infrared light (800 nm, 1.8 W / cm²), the temperature increased from 26.3 ℃ to 56.0 ℃. However, despite its potential for application, its photothermal conversion efficiency is still low and needs to be further improved. Summary of the invention
[0004] The present invention aims to solve the problem of low photothermal conversion efficiency of photothermal conversion materials in a wide spectral response range in the prior art, as well as the great challenges faced in applying them in photothermal and electric conversion devices, and provides an alkali lignin-loaded copper sulfide nanoparticle, a photothermal and electric device, and a preparation method and application thereof.
[0005] Specifically, one of the objectives of the present invention is to provide a method for preparing alkali lignin-loaded copper sulfide nanoparticles.
[0006] Another object of the present invention is to provide alkali lignin-loaded copper sulfide nanoparticles prepared by the above preparation method.
[0007] Another object of the present invention is to provide a photothermoelectric device.
[0008] Another object of the present invention is to provide an application of the above-mentioned alkali lignin-loaded copper sulfide nanoparticles or the above-mentioned photothermoelectric device in the field of photothermoelectric conversion and wearable devices.
[0009] The above-mentioned purpose of the present invention is achieved through the following technical solutions: The present invention provides a method for preparing alkali lignin-loaded copper sulfide nanoparticles, comprising the following steps: The alkali lignin nanoparticles and the copper salt solution were fully mixed and centrifuged, and the precipitate and the S-containing 2- The ion solution is fully mixed and then centrifuged, and the precipitate is dried to obtain alkali lignin-loaded copper sulfide nanoparticles.
[0010] Alkali lignin has abundant aromatic rings and hydroxyl groups, which can not only absorb visible light and near-infrared light, realize photothermal conversion, but also improve the dispersibility and stability of the material; the high light absorption capacity of copper sulfide enables it to effectively absorb visible light and near-infrared light. The present invention innovatively prepares alkali lignin into nanoparticles and then absorbs Cu in copper salt. 2+ Then with S 2- The alkali lignin-loaded copper sulfide nanoparticles were prepared by reaction. The stepwise reaction strategy adopted in the above preparation method effectively avoided the aggregation of particles. The obtained alkali lignin-loaded copper sulfide nanoparticles had a smaller particle size (which also means a larger specific surface area) and better dispersibility. This preparation method is conducive to promoting the alkali lignin nanoparticles to Cu 2+ Highly efficient adsorption, ensuring that 2- During the reaction, a uniform copper sulfide structure is formed, thereby improving the light-to-heat conversion efficiency and long-term stability of the obtained alkali lignin-loaded copper sulfide nanoparticles. In addition, the alkali lignin-loaded copper sulfide nanoparticles prepared based on the above preparation method have a large specific surface area, which further enhances the interaction between the obtained alkali lignin-loaded copper sulfide nanoparticles and light and improves their thermal conductivity.
[0011] Furthermore, the preparation method of the alkali lignin nanoparticles comprises the following steps: After the alkali lignin is fully dissolved in the solvent, the solution is centrifuged, the supernatant is mixed with water to prepare a suspension, the suspension is centrifuged, and the precipitate is the alkali lignin nanoparticles.
[0012] Furthermore, the solvent includes one or more of γ-valerolactone aqueous solution, methanol, ethanol, isopropanol, acetone, sodium hydroxide, dimethylsulfamide, dimethylformamide, and acetic acid.
[0013] Preferably, the solvent is a γ-valerolactone aqueous solution, which can better dissolve alkali lignin and improve its utilization rate.
[0014] More preferably, the volume ratio of γ-valerolactone to water is 1:(0.1-0.2).
[0015] Furthermore, the mass ratio of the alkali lignin to the solvent is 1:(50-150).
[0016] Furthermore, the mixing is prepared by ultrasonic mixing.
[0017] Furthermore, the ultrasound time is 30 to 60 min.
[0018] Furthermore, the centrifugal speed after sufficient dissolution is 1000-2000 g, wherein g represents the acceleration due to gravity.
[0019] Furthermore, the centrifugation time after sufficient dissolution is 15 to 30 min.
[0020] Furthermore, the suspension is centrifuged at a rate of 8000-12000 g.
[0021] Furthermore, the suspension is centrifuged for 30 to 60 min.
[0022] Preferably, the copper salt includes one or more of copper sulfate, copper chloride and copper acetate.
[0023] Furthermore, the mixing ratio of the alkali lignin nanoparticles and the copper salt is 1: (0.0004-0.004) g / mol.
[0024] Furthermore, the mixing is stirring.
[0025] Furthermore, the stirring time is 12 to 24 hours.
[0026] Furthermore, the centrifugal speed is 8000-10000 r / min.
[0027] Preferably, the centrifugation time is 15 to 30 min.
[0028] Furthermore, the S 2- The ions are selected from one or more of sodium sulfide nonahydrate, hydrogen sulfide, and sodium thiosulfate.
[0029] Furthermore, the precipitation, S 2- The mixing ratio of ions is 1: (0.0004~0.002) g / mol.
[0030] Furthermore, the drying is freeze-drying the precipitate for 1 to 3 days.
[0031] The present invention protects the alkali lignin-loaded copper sulfide nanoparticles prepared by the above preparation method.
[0032] The present invention protects a photothermal electric device, which is mainly composed of a photothermal conversion material and a thermoelectric conversion device, wherein the photothermal conversion material and the thermoelectric conversion device are electrically connected through electrodes in the thermoelectric conversion device; the photothermal conversion material is the above-mentioned alkali lignin-loaded copper sulfide nanoparticles.
[0033] The working principle of the above-mentioned photothermoelectric device is based on the combination of photothermal effect and thermoelectric effect. When the photothermoelectric device is exposed to light, the photothermal conversion material in the device converts light energy into heat energy, resulting in a temperature difference at both ends of the device. This temperature difference drives the migration of anions and cations inside the thermoelectric conversion device, and then gathers on both sides of the electrodes in the thermoelectric conversion device to form a potential difference or current. By measuring this potential difference or current, the detection and measurement of light radiation can be achieved.
[0034] The present invention combines the prepared photothermal conversion material with a thermoelectric conversion device to prepare an all-weather solar thermoelectric device with excellent performance, showing great potential in the basic research and practical application of self-powered wearable devices.
[0035] Furthermore, the thermoelectric conversion device includes a stacked structure arranged in sequence: a first electrode, a thermoelectric conversion material, and a second electrode.
[0036] Furthermore, the light-to-heat conversion material is disposed on the surface of the first electrode.
[0037] Specifically, the photothermal electric device comprises a stacked structure arranged in sequence: a photothermal conversion material, a first electrode, a thermoelectric conversion material and a second electrode. The photothermal conversion material is placed upward under a light source to effectively achieve photothermal electric conversion.
[0038] Furthermore, the thermoelectric conversion material is a hydrogel with thermoelectric function.
[0039] Preferably, as a preferred embodiment, the hydrogel with thermoelectric function is obtained by the following preparation method, and the preparation method comprises the following steps: Cyclodextrin-modified lignin sulfonate and adamantyl acrylate are added to a solvent containing thermoelectric materials and mixed evenly, and unsaturated carboxylic acid monomers, acrylamide monomers, metal ions and initiators are added to react fully to prepare a hydrogel with thermoelectric function; Furthermore, the preparation method of the cyclodextrin modified lignin sulfonate comprises the following steps: SI. Add cyclodextrin, p-toluenesulfonyl imidazole and alkaline reagent into water and mix well. After filtering, take the filtrate and adjust the pH to 7-8. After sufficient reaction, post-treatment, the intermediate product CDOTs is obtained. SII. Add the CDOTs and lignin sulfonate obtained in step SI into water and mix well, raise the temperature to 70-80°C for sufficient reaction, and post-treat to obtain cyclodextrin-modified lignin sulfonate.
[0040] Furthermore, in step SI, the cyclodextrin includes one or more of α-cyclodextrin, β-cyclodextrin, and γ-cyclodextrin. Cyclodextrin-modified lignin sulfonates obtained from cyclodextrins with different crystal structures can prepare thermoelectric hydrogels with good performance. Among them, β-cyclodextrin has a moderate inner diameter and is more suitable for inclusion of hydrophobic molecules (such as adamantane), thereby improving its solubility and stability, which is conducive to the subsequent construction of a hydrogel with a stable structure. Therefore, the cyclodextrin is preferably β-cyclodextrin.
[0041] Furthermore, in step SI, the mass ratio of cyclodextrin to p-toluenesulfonyl imidazole is (1.5~10):(1~3).
[0042] Furthermore, in step SI, the mass ratio of cyclodextrin to p-toluenesulfonyl imidazole is (1.5~10):1.
[0043] Furthermore, in step S1, the mixing is stirring mixing.
[0044] Furthermore, the stirring time is 2 to 4 h.
[0045] Furthermore, in step S1, the pH is adjusted using hydrochloric acid.
[0046] Furthermore, in step S1, the precipitation time is 18 to 36 h.
[0047] Further, in step S1, the post-treatment includes filtration, washing and recrystallization.
[0048] Furthermore, the filtering is to filter the precipitated material and collect the filter residue.
[0049] Furthermore, the washing is to wash the collected filter residue with ice water and acetone in sequence for 3 to 5 times.
[0050] Furthermore, the recrystallization is to remove soluble impurities by recrystallizing the washed filter residue with hot water at 80-100°C, and repeating the process 2-3 times.
[0051] Specifically, in step SI, the post-treatment includes filtering the precipitated material, collecting the filter residue, washing the filter residue with ice water and acetone for 3 to 5 times in sequence, collecting the washed filter residue and then recrystallizing it with 80 to 100 ° C hot water to remove soluble impurities, repeating 2 to 3 times, and the product obtained after recrystallization is the intermediate product CDOTs.
[0052] Furthermore, in step SII, the mass ratio of the CDOTs to the alkali lignin sulfonate is 1:(0.67-2.5).
[0053] Furthermore, in step SII, the mixing time is 1 to 2 h.
[0054] Furthermore, in step SII, the sufficient reaction time is 48 to 72 hours.
[0055] Furthermore, in step SII, the post-treatment includes dialysis and drying.
[0056] Furthermore, the dialysis is to dialyze the cooled mixture and collect the retained fluid.
[0057] Furthermore, the drying is to dry the retained solution after dialysis, and the drying is preferably freeze drying.
[0058] Specifically, in step SII, the post-treatment includes dialyzing the cooled mixture, and freeze-drying the retained solution after the dialyzate to obtain cyclodextrin-modified lignin sulfonate.
[0059] Further, as a preferred embodiment, the preparation method of adamantyl acrylate comprises the following steps: Si. Adding adamantane alcohol and triethylamine to an organic solvent and mixing well to obtain a mixed solution; Sii. Dilute acryloyl chloride with an organic solvent and dropwise add it into the mixed solution obtained in step Si to mix well, and then post-treat to obtain adamantyl acrylate.
[0060] Furthermore, in step Si, the adamantane alcohol is 1-adamantanol and / or 2-adamantanol.
[0061] Preferably, the adamantane alcohol is 1-adamantanol, which has stronger reactivity and is more likely to undergo nucleophilic substitution reaction with acryloyl chloride to form corresponding esters or amino compounds.
[0062] Furthermore, in step Si, the mass ratio of adamantane alcohol to triethylamine is 1:(1-3).
[0063] Furthermore, in step Si, the mixing time is 15 to 40 min.
[0064] Furthermore, in step Sii, the mass ratio of the acryloyl chloride to the organic solvent is 1:(1.67-10).
[0065] Furthermore, in step Sii, the mixing time is 18 to 36 hours.
[0066] Furthermore, in step Sii, the post-treatment includes filtration, washing, concentration and purification.
[0067] Furthermore, the filtration is to filter the mixed solution and collect the filtrate.
[0068] Furthermore, the washing is washing the filtrate with ice water and acetone in sequence for 1 to 3 times. Furthermore, the concentration is to collect the organic phase after washing and concentrate it by rotary evaporation at low temperature and reduced pressure at 4-15°C.
[0069] Furthermore, the purification is to purify the concentrated material using column chromatography, and the eluent is V 乙酸乙酯 :V 正己烷 =1:(15~20).
[0070] Specifically, in step Sii, the post-treatment includes filtering the mixed solution, collecting the filtrate, washing the filtrate with ice water and acetone for 1 to 3 times, collecting the washed organic phase and concentrating it by rotary evaporation at low temperature and reduced pressure at 4 to 15 °C, and purifying the concentrated substance by column chromatography, and the eluent is V 乙酸乙酯 :V 正己烷 =1:(15~20).
[0071] Furthermore, the mass ratio of the cyclodextrin-modified lignin sulfonate and adamantyl acrylate is (1-75): 1. The cyclodextrin-modified lignin sulfonate is used as a catalyst and a physical crosslinking agent, and adamantyl acrylate is used as a chemical crosslinking agent for the network structure. The crosslinking density at this mass ratio is more appropriate, and the mechanical properties of the prepared material are more excellent.
[0072] Furthermore, the mass ratio of the cyclodextrin modified lignin sulfonate to adamantyl acrylate is (1-40):1.
[0073] Preferably, the mass ratio of the cyclodextrin modified lignin sulfonate to adamantyl acrylate is 1:0.18.
[0074] Preferably, the thermoelectric material includes one or more of lithium chloride, sodium chloride, and potassium chloride. The above thermoelectric material can enhance the interaction between polymer chains (such as ionic bonds and hydrogen bonds), maintain the stability of the network structure, and improve the mechanical strength of the hydrogel.
[0075] Furthermore, the thermoelectric material is lithium chloride. Lithium chloride exhibits excellent thermoelectric performance, specifically a high thermoelectric figure of merit (i.e., ZT, ZT=σS²T / κ, where σ is electrical conductivity, S is Seebeck coefficient, T is temperature, and κ is thermal conductivity) and good thermal stability, and it has the characteristics of low cost and easy availability, so the thermoelectric material is preferably lithium chloride.
[0076] Furthermore, the concentration of the thermoelectric material is 0.1-3 mol / L.
[0077] Furthermore, the solvent is water or a moisturizing agent aqueous solution.
[0078] Furthermore, the moisturizing agent is glycerol and / or propylene glycol.
[0079] Preferably, the solvent is a moisturizing agent aqueous solution. Adding a moisturizing agent to the hydrogel can effectively enhance its moisturizing properties and slow down water loss, thereby improving the stability and efficiency of the photothermoelectric device.
[0080] More preferably, the moisturizing agent aqueous solution contains 甘油 :V 水 =1: (1~5).
[0081] Furthermore, the mixing time is 30 to 60 min.
[0082] Furthermore, the unsaturated carboxylic acid monomer is C3-C8 olefinic acid and / or C3-C8 acetylenic acid.
[0083] Furthermore, the unsaturated carboxylic acid monomer is C3-C5 olefinic acid and / or C3-C5 acetylenic acid.
[0084] Furthermore, the unsaturated carboxylic acid monomer includes one or more of acrylic acid, methacrylic acid, crotonic acid, propiolic acid, and butyric acid.
[0085] Furthermore, the acrylamide monomers include one or more of acrylamide, methacrylamide, and ethyl acrylamide.
[0086] Furthermore, the mass ratio of the unsaturated carboxylic acid monomer to the acrylamide monomer is 1:(0.8-1.5).
[0087] Furthermore, the metal ions are derived from one or more of stannous chloride, ferric chloride, calcium chloride, barium chloride, aluminum chloride, cobalt chloride, nickel chloride, cupric chloride, and silver chloride.
[0088] Preferably, the metal ion is stannous chloride. In the method for rapidly preparing multifunctional thermoelectric hydrogels in a metal-phenolic chemical system, compared with other transition metals (such as iron, cobalt, nickel, etc.), the introduction of stannous ions not only makes the hydrogel more uniform, but also significantly enhances its tensile properties.
[0089] Furthermore, the initiator is ammonium persulfate and / or potassium persulfate.
[0090] Furthermore, the sufficient reaction is that the cyclodextrin-modified lignin and the metal ions form a redox coordination system that can activate the initiator and quickly prepare the hydrogel.
[0091] Furthermore, the electrode is a polyaniline carbon fiber cloth electrode.
[0092] Furthermore, the polyaniline carbon fiber cloth electrode is prepared by a chemical oxidation deposition method, and comprises polyaniline and carbon fiber cloth, wherein the polyaniline is coated on the surface of the carbon fiber cloth.
[0093] Furthermore, the preparation scheme of the polyaniline carbon fiber cloth electrode includes the following steps: Aniline monomer and initiator were dissolved in acidic reagents respectively, carbon fiber cloth was immersed in aniline solution, and then the initiator solution was added to the aniline solution to react fully at low temperature, and polyaniline carbon fiber cloth electrode (PANI@CWF) was obtained by post-treatment.
[0094] Furthermore, the initiator is ammonium persulfate and / or potassium persulfate.
[0095] Furthermore, the molar ratio of the aniline monomer to the initiator is 1:(0.25~1).
[0096] Furthermore, the molar ratio of the aniline monomer to the initiator is 1:1.
[0097] Furthermore, the low temperature is an ice water bath.
[0098] Furthermore, the sufficient reaction time is 4 to 16 h, preferably 12 h.
[0099] Furthermore, the post-treatment includes washing and drying.
[0100] Furthermore, the washing is to rinse the carbon fiber cloth electrode containing polyaniline with deionized water for 3 to 6 times.
[0101] Furthermore, the drying is annealing in a vacuum oven at 60-80°C for 2-4 h.
[0102] Specifically, the post-treatment includes rinsing the carbon fiber cloth electrode containing polyaniline with deionized water for 3 times, and then annealing it in a vacuum oven at 60-80° C. for 2-4 h.
[0103] Furthermore, the photothermal electric device further comprises a stabilizing member having a hollow portion, and the photothermal conversion material is disposed in the hollow portion of the stabilizing member and connected to the electrode.
[0104] Preferably, the stabilizing member is an adhesive tape, which has double-sided adhesiveness, insulation and a certain thickness and can be used to prepare the stabilizing member.
[0105] Furthermore, the tape includes any one of polypropylene tape (VHB tape), polyurethane tape, acrylic tape, silicone tape, and polyester tape.
[0106] Preferably, the stabilizing member is a VHB tape. VHB tape has excellent adhesion, temperature resistance, aging resistance and good flexibility, can provide good lamination effects on different substrate surfaces, and adapt to various shapes and surfaces.
[0107] Furthermore, as a preferred embodiment, the method for preparing the photothermoelectric device comprises the following steps: Take two layers of PANI@CWF electrodes with a size of 1.5 cm×2.5 cm and encapsulate the hydrogel with thermoelectric function in a cylindrical mold made of VHB tape (the size of the VHB tape is 1.5 cm×1.5 cm, and there is a circular cavity with a diameter of 1.2 cm and a height of 1.2 cm inside). In this way, a "sandwich" structure thermoelectric conversion device assembled in the order of electrode-thermoelectric functional hydrogel-electrode is formed. Subsequently, a VHB tape with the same size of 1.5 cm×1.5 cm is glued to the upper electrode, which also has a circular cavity with a diameter of 1.2 cm. In this cavity, alkali lignin-loaded copper sulfide nanoparticles are filled to obtain a photothermoelectric conversion device.
[0108] The present invention also protects the application of the above-mentioned alkali lignin-loaded copper sulfide nanoparticles or the above-mentioned photothermoelectric device in the field of wearable devices.
[0109] Compared with the prior art, the present invention has the following beneficial effects: The present invention innovatively firstly combines the alkaline lignin nanoparticles and the Cu in the copper salt 2+ After adsorption with S 2- The reaction prepared an alkali lignin-loaded copper sulfide nanoparticle, which was then assembled with a hydrogel with thermoelectric function to obtain a photothermoelectric device. Among them, the alkali lignin-loaded copper sulfide nanoparticles as a photothermal conversion material have excellent photothermal conversion efficiency and long-term stability, which is the key to improving the performance of photothermoelectric devices; the hydrogel with thermoelectric function maintains excellent thermoelectric properties and water retention properties, and enhances the stability and durability of the hydrogel; the photothermoelectric device assembled by the two not only has excellent photothermoelectric performance, but also has a long service life, which fully proves the huge potential and application prospects of alkali lignin-loaded copper sulfide nanoparticles in the fields of photothermoelectric devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0110] Figure 1 This is a structural diagram of the photothermoelectric device prepared in Example 1.
[0111] Figure 2This is the infrared spectrum of the alkali lignin-loaded copper sulfide nanoparticles prepared in Example 1.
[0112] Figure 3 This is a SEM image of the alkali lignin-loaded copper sulfide nanoparticles prepared in Example 1.
[0113] Figure 4 This is the SEM image of the alkali lignin-loaded copper sulfide nanoparticles prepared in Comparative Example 1.
[0114] Figure 5 The temperature variation diagram of the photothermal conversion materials prepared in Example 1, Comparative Example 1 and Comparative Example 2 under simulated solar radiation at different times.
[0115] Figure 6 The temperature change curve of the alkali lignin-loaded copper sulfide nanoparticles prepared in Example 1 under different light powers (a), the relationship curve between the temperature change and the light power density under different solar radiation intensities (b), and the reversible temperature change diagram under simulated solar radiation (100 mW / cm²) (c).
[0116] Figure 7 The mass change curve (a) and antifreeze optical graph (b) of the thermoelectric hydrogel prepared in Example 1.
[0117] Figure 8 The open circuit voltage-time curve (a), power-time curve (b), and output voltage stability graph (c) of the photothermoelectric conversion device prepared in Example 1 are shown. DETAILED DESCRIPTION
[0118] The present invention is further described below in conjunction with the accompanying drawings and specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0119] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0120] Alkali lignin was provided by Shanghai Changfa New Materials Co., Ltd.
[0121] Figure 6 a means Figure 6 Figure a in the figure; Figure 6 b means Figure 6 The naming of other figures is similar.
[0122] Example 1 Alkali lignin loaded copper sulfide nanoparticles, thermoelectric functional hydrogel, photothermoelectric conversion device and preparation method thereof 1. Preparation of Alkali Lignin Supported Copper Sulfide Nanoparticles (AL-NPs@CuS-1) At room temperature (25 °C), 200 mg of alkali lignin (AL) was added to 20 mL of γ-valerolactone / water solution (GVL / H2O), where V GLY :V H2O =87:13. Subsequently, ultrasonic treatment was performed for 30 min to ensure that the alkali lignin was completely dissolved. Then, centrifugation was performed at 2000 g for 30 min, and the supernatant obtained was a saturated alkali lignin solution. This solution was quickly injected into water to form a suspension with a total volume of 200 mL. Thereafter, centrifugation was performed at 10000 g for 30 min to precipitate alkali lignin nanoparticles (AL-NPs). The precipitated AL-NPs were dispersed in 200 mL of ultrapure water, and 3.9 g of copper sulfate pentahydrate (CuSO4·5H2O) was added and stirred at room temperature for 12 h. Then centrifugation was performed at 8000 r / min for 15 min, the supernatant was removed and the precipitate was retained. The obtained precipitate was dispersed in 100 mL of deionized water, 100 mg of sodium sulfide nonahydrate (Na2S·9H2O) was added, and stirred in a water bath at 60 ℃ for 5 h. Centrifugation was performed again at 8000 r / min for 15 min, the supernatant was removed, and the precipitate was retained. Finally, the precipitate was freeze-dried in vacuum for 2 days to obtain AL-NPS@CuS-1.
[0123] 2. Preparation of Cyclodextrin-modified Lignin Sulfonate (LS-CD) 36.3 g of β-cyclodextrin and 6.67 g of 1-toluenesulfonyl imidazole were added to 250 mL of deionized water and stirred vigorously at room temperature for 3 h. After adding 50 mL of 10wt% NaOH solution, stirring was continued for 30 min. The unreacted insoluble matter was removed by filtration, and then 1 M HCl solution was added to adjust the pH value of the filtrate to pH = 7.5. The obtained mixture was precipitated at low temperature for 18 h, and then filtered to collect the filter residue, which was washed with ice water and acetone three times to obtain a crude product. The crude product was recrystallized in hot water three times to obtain the product CDOTs. 6.5 g of lignin sulfonate was dissolved in 150 mL of deionized water and stirred thoroughly to obtain a clear solution. 6.5 g of CDOTs was added, and the mixture was stirred vigorously at room temperature for 2 h, then heated to 80 °C and refluxed for 72 h. After cooling, it was transferred to the dialysis bag of MWC 3500 for 3 days, and the retained solution after dialysis was freeze-dried to obtain a yellow or light yellow product, which was LS-CD.
[0124] 3. Preparation of Adamantyl Acrylate (ADA) 3.04 g of 1-adamantanol and 60 mL of anhydrous dichloromethane were added to the reactor and stirred until fully dissolved, then 3 g of triethylamine was added. The mixed solution was kept stirring at 0 °C for 40 min. 3.62 g of acryloyl chloride diluted with 25 mL of anhydrous dichloromethane was added dropwise to the mixed solution at 0 °C through a constant pressure dropping funnel. After the dropwise addition, the mixture was slowly warmed to room temperature and continued to stir for 18 h. After the addition, the insoluble matter was filtered out and the filtrate was collected; the filtrate was washed three times with 0.1 M HCl aqueous solution, 0.5 wt% NaHCO3 solution, and distilled water, respectively, and the organic phase was collected and concentrated by low-temperature vacuum rotary evaporation at 4 °C. It was purified by column chromatography, in which the eluent was V 乙酸乙酯 :V 正己烷 =1:15, and the product ADA was obtained, which was stored at low temperature for future use.
[0125] 4. Preparation of Thermoelectric Functional Hydrogel (LAMOH-1) 0.0144 g LS-CD and 80 μL methanol solution containing ADA (0.01 g / ml) were added to a 1.5 mol / L lithium chloride glycerol / water solution (7 mL), where V 甘油 :V 水 =1:2 and stirred at room temperature for 30 min. Then 0.02 g of stannous chloride (SnCl2) was added, followed by 0.96 g of acrylamide (AM) and 0.96 g of acrylic acid (AA), and finally 0.024 g of ammonium persulfate (APS) to obtain the thermoelectric functional hydrogel LAMOH-1.
[0126] 5. Preparation of polyaniline carbon fiber cloth electrode First, carbon fiber cloth (CWF) was ultrasonically cleaned with ethanol and deionized water for 30 min. Then, 0.025 mol of ANI monomer was dissolved in 2.0 mol / L H2SO4 solution (25 mL) by magnetic stirring and reacted in an ice-water bath for 1 h to obtain solution A. Then, 0.025 mol of APS was dissolved in 2.0 mol / L H2SO4 solution (25 mL) to prepare solution B. The cleaned CWF was used as a supporting substrate, and polyaniline nanorod arrays were directly assembled on it by a simple chemical oxidation deposition process. CWF was vertically immersed in solution A, and then solution B was added to solution A and reacted in an ice-water bath with magnetic stirring for 12 h. The obtained CWF containing polyaniline was rinsed with deionized water several times and then annealed in a vacuum oven at 60 ℃ for 2 h to finally obtain the product, which was labeled as PANI@CWF.
[0127] 6. Preparation of Photothermal Electricity Conversion Devices Take two layers of PANI@CWF electrodes with a size of 1.5 cm×2.5 cm and encapsulate the thermoelectric functional hydrogel in a cylindrical mold made of VHB tape (the size of the VHB tape is 1.5 cm×1.5 cm, and there is a circular cavity with a diameter of 1.2 cm and a height of 1.2 cm inside). In this way, a "sandwich" structure thermoelectric conversion device assembled in the order of electrode-thermoelectric functional hydrogel-electrode is formed. Subsequently, VHB tape of the same size of 1.5 cm×1.5 cm is glued to the upper electrode, which also has a circular cavity with a diameter of 1.2 cm. In this cavity, AL-NPS@CuS-1 is filled to obtain a photothermoelectric conversion device. The structural schematic diagram of the photothermoelectric device is shown in the figure. Figure 1 shown.
[0128] Example 2 Alkali lignin loaded copper sulfide nanoparticles, thermoelectric functional hydrogel, photothermoelectric device and preparation method thereof The difference from Example 1 is that the glycerol / water solution in step 4 is changed to water.
[0129] The other steps and conditions were the same as those in Example 1, and the alkali lignin-loaded copper sulfide nanoparticles, the thermoelectric functional hydrogel LAMOH-2, and the photothermoelectric device based on LAMOH-2 were obtained in sequence. Example 3 Alkali lignin-loaded copper sulfide nanoparticles, thermoelectric functional hydrogel, photothermoelectric device and preparation method thereof The difference from Example 1 is that the thermoelectric material lithium chloride in step 4 is replaced by sodium chloride.
[0130] The other steps and conditions were the same as those in Example 1, and alkali lignin-loaded copper sulfide nanoparticles, thermoelectric functional hydrogel LAMOH-3, and a photothermoelectric device based on LAMOH-3 were obtained in sequence.
[0131] Comparative Example 1 Alkali lignin-loaded copper sulfide nanoparticles and preparation method thereof The difference from Example 1 is that the alkali lignin nanoparticles in step 1 first adsorb Cu 2+ , and then with S 2- The reaction was replaced by alkali lignin nanoparticles and Cu 2+ , S 2- A blending reaction occurs, and the specific preparation method comprises the following steps: At room temperature (25 °C), 200 mg of alkali lignin (AL) was added to 20 mL of γ-valerolactone / water solution (GVL / H2O), where V GLY :V H2O=87:13. Subsequently, ultrasonic treatment was performed for 30 min to ensure that the alkali lignin was completely dissolved. Then, centrifugation was performed at 2000 g for 30 min, and the supernatant obtained was a saturated alkali lignin solution. This solution was quickly injected into water to form a suspension with a total volume of 200 mL. Thereafter, centrifugation was performed at 10000 g for 30 min to precipitate alkali lignin nanoparticles (AL-NPs). The precipitated AL-NPs were dispersed in 50 mL of ultrapure water and mixed with CuSO4 solution (0.2 M, 10 mL) under stirring at 600 rpm / min. The mixed solution was heated to 80 °C, and Na2S solution (0.2 M, 10 mL) was added dropwise to react for 30 min. The reacted solution was dialyzed for 48 h, concentrated by rotary evaporation and dried at 50 °C to obtain AL-NPs@CuS-4.
[0132] In the above comparative example 1, the alkaline lignin nanoparticles and Cu 2+ , S 2- The method for preparing alkali lignin-loaded copper sulfide nanoparticles by a blending reaction is the method disclosed in the prior art (Xie Y, Qian Y, Li Z, et al. Near-infrared-activated efficient bacteria-killing by lignin-based copper sulfidenanocomposites with an enhanced photothermal effect and peroxidase-likeactivity[J]. ACS Sustainable Chemistry&Engineering, 2021, 9(18): 6479-6488.).
[0133] Comparative Example 2 An alkali lignin-loaded copper sulfide composite material and preparation method thereof The difference from Example 1 is that the alkali lignin in step 1 is not prepared into nanoparticles loaded with copper sulfide in advance, but copper sulfide is directly loaded in the form of alkali lignin. The specific preparation method includes the following steps: Alkali lignin (AL) was dispersed in 200 mL ultrapure water, and 3.9 g of copper sulfate pentahydrate (CuSO4·5H2O) was added and stirred at room temperature for 12 h. Then centrifuged at 8000 r / min for 15 min, the supernatant was removed and the precipitate was retained. The obtained precipitate was dispersed in 100 mL deionized water, 100 mg of sodium sulfide nonahydrate (Na2S·9H2O) was added, and stirred in a 60 ℃ water bath for 5 h. Centrifuged again at 8000 r / min for 15 min, the supernatant was removed, and the precipitate was retained. Finally, the precipitate was freeze-dried in vacuum for 2 days to obtain the alkali lignin-based photothermal conversion material (AL @CuS).
[0134] Experimental examples: Performance characterization of photothermal conversion materials, thermoelectric functional hydrogels, and photothermal electric conversion devices 1. Characterization of structure and morphology of photothermal conversion materials In order to characterize the successful preparation of the AL-NPs@CuS-1 composite material prepared in Example 1, infrared spectroscopy was performed. Figure 2 As shown, 1113 cm -1 and 1513 cm -1 The characteristic peaks at 617 cm-1 correspond to the CO and aromatic skeleton vibrations of AL. -1 The peak corresponding to the Cu-S stretching is also shown at , which indicates the successful construction of the AL-NPs@CuS-1 composite material. Further, the alkali lignin-supported copper sulfide nanoparticles prepared in Example 1 and Comparative Example 1 were characterized by SEM. Figure 3 As shown in the figure, the particle size of the AL-NPs@CuS-1 composite material prepared in Example 1 is about 100 nm, and the particles are small and evenly dispersed, which provides a basis for its excellent photothermal performance. 2+ , and then with S 2- In Comparative Example 1, although alkali lignin was also used to prepare nanoparticles, it reacted with Cu 2+ and S 2- The blending reaction resulted in uneven particle size and aggregation of the prepared nanoparticles ( Figure 4 ), which in turn affects the performance of photothermal conversion materials.
[0135] The SEM images of the alkali lignin-supported copper sulfide nanoparticles prepared in Examples 2-3 are similar to the SEM images of the alkali lignin-supported copper sulfide nanoparticles in Example 1, and are not described again here.
[0136] 2. Characterization of photothermal properties of photothermal conversion materials Alkali lignin-loaded copper sulfide nanoparticles or alkali lignin-loaded copper sulfide composite material powders were piled into a circle with a diameter of 1 cm and a thickness of 1 mm, and placed under a CEL-HXUV300-T3 xenon lamp for 16 min. The powders were photographed every 1 min using a FLIR T530 thermal imaging camera. By comparing the three methods for preparing photothermal conversion materials in Example 1 and Comparative Examples 1-2, respectively, alkali lignin was prepared into nanoparticles and then adsorbed with Cu 2+, and then the alkali lignin was used to prepare the photothermal conversion materials. 2+ Then with S 2- Reaction (Example 1), alkali lignin prepared nanoparticles and Cu 2+ , S 2- Blending reaction (Comparative Example 1), and alkali lignin directly dispersed in water to adsorb Cu 2+ Then with S 2- Reaction (Comparative Example 2), the result is as follows Figure 5 As shown, in Comparative Example 1, the alkali lignin-loaded copper sulfide nanoparticles prepared therein had uneven particle sizes and aggregation, which affected the stability of their photothermal conversion performance. After one week, their stability decreased by about 10%; in Comparative Example 2, the alkali lignin was not prepared into nanoparticles in advance, which limited the loading capacity of copper sulfide, thereby hindering the improvement of its photothermal performance. The photothermal conversion material prepared by the preparation method adopted in Example 1 not only has good photothermal conversion performance, but also has excellent long-term stability. The photothermal conversion performance of the obtained alkali lignin-loaded copper sulfide nanoparticles was measured after being placed for one week, and its photothermal conversion performance was basically the same as that of the freshly prepared material. This is because the stepwise reaction strategy adopted in Example 1 effectively avoids particle aggregation, and the obtained AL-NPs@CuS-1 composite material can be evenly dispersed and has a better particle size. This preparation method promotes the alkali lignin nanoparticles to Cu 2+ Highly efficient adsorption ensures that 2- A uniform copper sulfide structure is formed during the reaction, thereby improving the material's photothermal conversion efficiency and long-term stability.
[0137] Furthermore, the photothermal conversion properties of the photothermal conversion material in Example 1 were characterized by simulating different light power densities under sunlight irradiation. Figure 6 a and 6b, the surface temperature of alkali lignin-loaded copper sulfide nanoparticles increased significantly with the increase of the light power density of simulated sunlight, and the maximum temperature rise (ΔT) was linearly related to the light power density, which proved that the temperature of the composite material can be precisely controlled by the light power density. Figure 6c explored the cyclic characteristics of the photothermal conversion effect of alkali lignin-loaded copper sulfide nanoparticles. As can be seen from the figure, the photothermal conversion effect of alkali lignin-loaded copper sulfide nanoparticles remains unchanged in three simulated solar radiation cycles, and has good photothermal conversion effect cyclic characteristics. All of the above results show that the alkali lignin-loaded copper sulfide nanoparticles prepared in this application have good photothermal performance and can effectively convert light energy into heat energy, and the resulting heat energy is further used by thermoelectric conversion materials to convert into electrical energy.
[0138] 3. Characterization of the antifreeze and water retention properties of thermoelectric functional hydrogels The antifreeze and water retention performance of the thermoelectric functional hydrogel in Example 1 was characterized. Figure 7 As shown in a, after storage at 25°C for 7 days, the LAMOH-1 hydrogel can still maintain more than 70% of its initial weight, indicating that the addition of humectant glycerol during the preparation of thermoelectric functional hydrogel can keep the water content of the hydrogel within a higher range, which is beneficial to maintaining the stability of the hydrogel and extending its service life.
[0139] In order to further study the antifreeze properties of LAMOH-1 hydrogel, the present invention verifies the conductivity of the hydrogel under low temperature conditions. The results are as follows Figure 7 As shown in b, the small light bulb in the hydrogel circuit can remain lit regardless of room temperature or -20°C, proving that it can still maintain electron transmission under low temperature conditions and has excellent antifreeze properties.
[0140] 4. Performance testing of photothermoelectric devices The energy density of the photothermoelectric device in Example 1 was tested to characterize its photoelectric conversion performance, with a value of ≤0.3 mV min -1 The voltage is close to saturation state defined by the rate of change of voltage. After that, the power output level is obtained by externally connecting various resistors, and the energy density during the 1-hour discharge process is calculated by integrating the output power curve. The average power density under external load is calculated using the equation P=E / Δt, where Δt is the total duration of the discharge stage in a thermal cycle, and the instantaneous output power is obtained by multiplying the voltage and current.
[0141] The results are as follows Figure 8 As shown, the photothermoelectric device is 2 The open circuit voltage reached 0.297 V under the light intensity of 200 mW / cm 2 The open circuit voltage reaches up to 0.403 V ( Figure 8 a). At the same time, at a light intensity of 200 mW / cm 2 Down, Figure 8b shows the power-time curve of the photothermoelectric conversion device in Example 1 connected in series with a 3 kΩ resistor box. The energy density reaches 628 J·m in 1 hour. -2 At a light intensity of 100 mW / cm 2 Under this condition, the open circuit voltage fluctuates slightly around the saturated open circuit voltage and remains so for at least 28 h (e.g. Figure 8 c), indicating that the organic photothermoelectric device has long-term output stability. This shows that the photothermoelectric conversion device prepared by the present invention has high photothermoelectric conversion efficiency and output stability.
[0142] In summary, the present invention innovatively firstly reacts the alkaline lignin nanoparticles with the Cu 2+ After adsorption with S 2- The reaction prepared an alkali lignin-loaded copper sulfide nanoparticle, which was then assembled with a hydrogel with thermoelectric function to obtain a photothermoelectric device. Among them, the alkali lignin-loaded copper sulfide nanoparticles as a photothermal conversion material have excellent photothermal conversion efficiency and long-term stability, which is the key to improving the performance of photothermoelectric devices; the hydrogel with thermoelectric function maintains excellent thermoelectric properties and water retention properties, and enhances the stability and durability of the hydrogel; the photothermoelectric device assembled by the two not only has excellent photothermoelectric performance, but also has a long service life, which fully proves the huge potential and application prospects of alkali lignin-loaded copper sulfide nanoparticles in the field of photothermoelectric devices.
[0143] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing alkali lignin-loaded copper sulfide nanoparticles, characterized in that: The following steps are involved: The alkali lignin nanoparticles and the copper salt solution were fully mixed and centrifuged, and the precipitate and the S-containing 2- The ion solution is fully mixed and then centrifuged, and the precipitate is dried to obtain alkali lignin-loaded copper sulfide nanoparticles.
2. The preparation method according to claim 1, characterized in that: The preparation method of the alkali lignin nanoparticles comprises the following steps: After the alkali lignin is fully dissolved in the solvent, the solution is centrifuged, the supernatant is mixed with water to prepare a suspension, the suspension is centrifuged, and the precipitate is the alkali lignin nanoparticles.
3. The preparation method according to claim 1, characterized in that: The S 2- The ions are selected from one or more of sodium sulfide nonahydrate, hydrogen sulfide, and sodium thiosulfate.
4. Alkali lignin-loaded copper sulfide nanoparticles prepared by the preparation method according to any one of claims 1 to 3.
5. A photothermoelectric device, characterized in that: The photothermal electric device is mainly composed of a photothermal conversion material and a thermoelectric conversion device, wherein the photothermal conversion material and the thermoelectric conversion device are electrically connected through electrodes in the thermoelectric conversion device; the photothermal conversion material is the alkali lignin-loaded copper sulfide nanoparticles as described in claim 4.
6. The photothermoelectric device according to claim 5, characterized in that: The thermoelectric conversion device includes a stacked structure arranged in sequence: a first electrode, a thermoelectric conversion material, and a second electrode.
7. The photothermoelectric device according to claim 6, characterized in that: The light-to-heat conversion material is disposed on the surface of the first electrode.
8. The photothermoelectric device according to claim 6, characterized in that: The thermoelectric conversion material is a hydrogel with thermoelectric function.
9. The photothermoelectric device according to claim 8, characterized in that: The method for preparing the hydrogel with thermoelectric function comprises the following steps: Cyclodextrin-modified lignin sulfonate and adamantyl acrylate are added to a solvent containing thermoelectric materials and mixed evenly, and unsaturated carboxylic acid monomers, acrylamide monomers, metal ions and initiators are added to fully react to prepare a hydrogel with thermoelectric function.
10. Application of the alkali lignin-loaded copper sulfide nanoparticles according to claim 4 or the photothermoelectric device according to any one of claims 5 to 9 in the field of photothermoelectric conversion or the field of wearable devices.
Citation Information
Patent Citations
Composite material of lignin / metal nanoparticles and preparation method of composite material
CN104277468A
Magnetic nanoparticle based on alkali lignin, preparation method of magnetic nanoparticle and application of magnetic nanoparticle to copper ion adsorption
CN108671899A
Photo-thermal lignin nanoparticle, lignin-based near-infrared light response shape memory polyurethane, and preparation method and application of lignin-based near-infrared light response shape memory polyurethane
CN116535673A